Recognizing service users' diversity: social identity narratives of British Pakistanis in a mental health context. Issue 3 (17th February 2021) - Hussain, Basharat; Sheikh, Abdullah Zafar; Repper, Julie; Stickley, Theodore; Timmons, Stephen; Shah, Mahmood Hussain
Abstract : Purpose: This study aims to investigate how British Pakistani people talk about their social identity, in the context of mental health, and how this shapes their experiences and perceptions of care delivered by the National Health Service, UK. Design/methodology/approach: Eight narrative interviews were conducted among members of the Pakistani community living in a city in the UK. The data were analyzed using a narrative analysis approach using "social identity" as a theoretical lens. Findings: Considering Pakistani service users as a single social entity, and responding with generic approaches in meeting their mental health needs, may not be helpful in achieving equitable treatment. Study participants reject a simple conceptualization of race and ethnicity and how a response based upon stereotypes is woefully inadequate. The study revealed that people from one ethnic or national background cannot be assumed to have a fixed social identity. Originality/value: This study broadens understanding of how people from a single ethnic background may construct and view their social identities markedly different to others from the same ethnic group. This has implications for service providers in understanding how their clients' social identity is treated and understood in practice.